Genetic and Evolutionary Analysis of Porcine Deltacoronavirus in Guangxi Province, Southern China, from 2020 to 2023 - Biao Li; Yeheng Gao; Yan Ma; Kaichuang Shi; Yuwen Shi; Shuping Feng; Yanwen Yin; Feng Long; Wenchao Sun (Microorganisms, 2024)
Porcine deltacoronavirus (PDCoV) has shown large-scale global spread since its discovery in Hong Kong in 2012. In this study, a total of 4897 diarrheal fecal samples were collected from the Guangxi province of China from 2020 to 2023 and tested using RT-qPCR. In total, 362 (362/4897, 7.39%) of samples were positive for PDCoV. The S, M, and N gene sequences were obtained from 34 positive samples after amplification and sequencing. These PDCoV gene sequences, together with other PDCoV S gene reference sequences from China and other countries, were analyzed. Phylogenetic analysis revealed that the Chinese PDCoV strains have diverged in recent years. Bayesian analysis revealed that the new China 1.3 lineage began to diverge in 2012. Comparing the amino acids of the China 1.3 lineage with those of other lineages, the China 1.3 lineage showed variations of mutations, deletions, and insertions, and some variations demonstrated the same as or similar to those of the China 1.2 lineage. In addition, recombination analysis revealed interlineage recombination in CHGX-MT505459-2019 and CHGX-MT505449-2017 strains from Guangxi province. In summary, the results provide new information on the prevalence and evolution of PDCoV in Guangxi province in southern China, which will facilitate better comprehension and prevention of PDCoV.